Selective formation of a C3-symmetric P-stereogenic tris(phosphine) via platinum-catalyzed asymmetric alkylation of a tris(secondary phosphine). Issue 24 (31st December 2015) - Xu, Zhiming; Cain, Matthew F.; Rupert, Alexander V.; Glueck, David S.; Golen, James A.; Rheingold, Arnold L.
Graphical abstract: Abstract: Alkylation of MeC(CH2 PHPh)3 1 with 2-cyanobenzyl bromide and NaOSiMe3 using the catalyst precursor Pt(( R, R )-Me-DuPhos)(Ph)(Cl) gave a mixture of tris(phosphines) enriched in C 3 -MeC(CH2 PPh(CH2 ( o- C6 H4 CN))3 3 ; Cu-catalyzed phosphination yielded C 1 -enriched3 . Oxidation of3 by sulfur or H2 O2 formed MeC(CH2 P(E)Ph(CH2 ( o -C6 H4 CN))3 (E = S4 ; E = O5 ). Repeated recrystallization gave a low yield of ( R, R, R )-4, which was crystallographically characterized. Tris(phosphine)3 was formed with a diastereomeric ratio (dr = C 3 / C 1 ) of 2.1(2) and enantiomeric ratios of 54(10) and 3.8(7) for C 3 -3 and C 1 -3 respectively, which showed that the selectivity of the triple alkylation was not the same at each site (substrate control).